2011
DOI: 10.1177/0194599811400686
|View full text |Cite
|
Sign up to set email alerts
|

French Validation of the NOSE and RhinoQOL Questionnaires in the Management of Nasal Obstruction

Abstract: The French versions of both questionnaires appear to be as reliable, valid, and sensitive to change as the English versions. Their association was strong, allowing assessment of nasal obstruction in all its dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
81
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 20 publications
14
81
2
2
Order By: Relevance
“…The median follow-up was 13.5 months (8. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. No nasolacrimal duct complication was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up was 13.5 months (8. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. No nasolacrimal duct complication was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the quantity of material is known, and postoperative QoL scores in this small series were near those of the normal population. 2 …”
Section: Discussionmentioning
confidence: 99%
“…22 This scale has been evaluated in multiple studies, has been translated into multiple different languages, and has been shown to be both reliable and validated. 8,23,24 Aging Face and Facial Rejuvenation Assessment Scales…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Son choix sera d'autant plus pertinent qu'il pourra appréhender les résistances nasales du patient. Pour se faire, le questionnaire d'évaluation de l'obstruction nasale, ou Nasal Obstruction Symptom Evaluation (NOSE) [26], constitue un bon outil et est validé en langue française [27] (Tableau I). Par ailleurs, l'ajout d'un humidificateur chauffant permet de diminuer les résistances nasales [28].…”
Section: Résistances Nasalesunclassified